IMPLEMENTASI NILAI-NILAI KE NU-an DALAM MENANAMKAN KARAKTER SEMANGAT KEBANGSAAN PADA SISWA KELAS XII IPS 1 SMA NU CILEDUG - muhammadfachjrikurniawan; Hamidah; Ali muda pahlevi; Siti Nur Amanah; Husnul Khatimah (UI Cirebon (Universitas Islam Cirebon), 2024)
This research aims to explore the implementation of NU values in instilling the character of national spirit in class XII IPS 1 SMA NU Ciledug. This research uses a qualitative descriptive research method. Data was collected through interviews and observations with related teachers and students as well as documentation. The research results show that the values of Tawassuth (moderate), Tawazun (balanced), and Tasamuh (tolerant) in the Islamic teachings of Ahlussunnah Wal Jamaah are well integrated in learning activities, such as istigosah, Marhaban Al Barzanji, and sholawatan. The implementation of Tawassuth values is reflected in efforts to avoid extremism, while Tasamuh values are implemented through an attitude of tolerance towards religious differences. Tawazun values are implemented through extracurricular activities, flag ceremonies, and mutual cooperation are also part of the implementation of national values. Even though the process of cultivating the character of a national spirit is already going well, research shows that optimizing results requires further support from various parties, including parents, teachers and the surrounding environment.